Pengaruh Penggunaan Media Flash Card Terhadap Perkembangan Kognitif Dan Kemampuan Berhitung Sederhana Anak TK (The Effect of Using Flash Card Media on Cognitive Development and Simple Numeracy Skills in Kindergarten Children) - Nurul Alfiyah; Rudy Sumiharsono; Eges Triwahyuni (LP. Ma'arif Janggan Magetan, 2023)
The aim of the research was to find out whether using flashcard media could improve cognitive development and simple numeracy skills for groups A and B at AN-NUR Kindergarten Karangharjo Glenmore. Variable X (media flashcard) has 9 indicators, Y1 (cognitive development) has 6 indicators. Variable Y2 (simple numeracy skills) there are 22 indicators. The research design uses causal quantitative. The method of determining the area by purposive sampling area. The population research population research technique consisted of 31 children in groups A and B. Data collection techniques: 1). observation, 2). interview, 3). document. The results of the interviews are then processed into several instrument tests of validity and reliability tests, then the classic assumption test includes the normality test, homogeneity test, autocorrelation test, and heteroscedasticity test, and finally is the hypothesis test which includes t test and F test. Results of t X test against Y1 sig<0.05(0.000).